2015
DOI: 10.1371/journal.pone.0136988
|View full text |Cite
|
Sign up to set email alerts
|

Polysomnographic Assessment of Sleep Comorbidities in Drug-Naïve Narcolepsy-Spectrum Disorders—A Japanese Cross-Sectional Study

Abstract: This is a large cross-sectional study which aimed to investigate comorbidity rate, degree of sleep-related breathing disorder, polysomnigraphically diagnosible rapid eye movement sleep behavior disorder/rapid eye movement sleep without atonia and periodic limb movements during sleep in Japanese drug-naïve patients with narcolepsy-spectrum disorders. A total of 158 consecutive drug naïve patients with narcolepsy with cataplexy, 295 patients with narcolepsy without cataplexy and 395 patients with idiopathic hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
9
0
1
Order By: Relevance
“…Classically, sleep efficiency is greater than 90% in patients with IH (4, 16, 18, 24, 25), although some studies have reported mean values in the high 80s (15, 19). The tendency for high sleep efficiency is somewhat at odds with the recently-proposed hypothesis that patients with IH have fragmented sleep, as evidenced by more sleep stage changes, more N1 sleep, and more awakenings per hour than either controls or patients with narcolepsy type 1 (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, sleep efficiency is greater than 90% in patients with IH (4, 16, 18, 24, 25), although some studies have reported mean values in the high 80s (15, 19). The tendency for high sleep efficiency is somewhat at odds with the recently-proposed hypothesis that patients with IH have fragmented sleep, as evidenced by more sleep stage changes, more N1 sleep, and more awakenings per hour than either controls or patients with narcolepsy type 1 (26).…”
Section: Introductionmentioning
confidence: 99%
“…The tendency for high sleep efficiency is somewhat at odds with the recently-proposed hypothesis that patients with IH have fragmented sleep, as evidenced by more sleep stage changes, more N1 sleep, and more awakenings per hour than either controls or patients with narcolepsy type 1 (26). Abnormalities in slow wave sleep percentage have been proposed but inconsistently observed (1, 4, 16, 18, 19, 25, 26). A single, small study has suggested an increase in spindle activity in IH patients compared to those with narcolepsy (type unspecified) (27).…”
Section: Introductionmentioning
confidence: 99%
“…In our clinical experience, sometimes, these associated sleep disorders are misdiagnosed as the primary conditions, and the diagnosis and treatment of narcolepsy is delayed. NREM parasomnias, REM parasomnias, OSA as well as nocturnal movement disorders are all commonly reported among narcolepsy patients [43,44]. In our experience, these findings on a sleep study have resulted in misdiagnosis of another primary sleep disorder (Fig.…”
Section: Sleep-related Co-morbiditiesmentioning
confidence: 82%
“…Periodic limb movements of sleep (PLMS) refers to a movement disorder that presents as rhythmic, repetitive myoclonic-like jerking of the limbs that disturb sleep [20]. PLMS has been reported in up to 75 % of patients with narcolepsy, often with higher indexes of movements per hour (>15/h) compared to controls [43,44]. Similarly, REM behavior disorder which requires repeated episodes of dream enactment with sleep-related vocalization and/or complex motor behavior with polysomnographic evidence of REM without atonia is frequently reported.…”
Section: Periodic Limb Movements Of Sleep and Rem Behavior Disordermentioning
confidence: 99%
“…Além da difi culdade primária de manutenção do sono, própria da defi ciência de hipocreti na, pode haver, em associação, difi culdades secundárias de se manter o sono, devido a certos transtornos de sono associados à narcolepsia, como, por exemplo, a síndrome da apneia obstruti va de sono, os movimentos periódicos dos membros e o transtorno comportamental do sono REM, que são comuns nesses pacientes 25 .…”
Section: Fragmentação Do Sono Noturnounclassified